NATIONALISM AND THE PROCESS OF CATALONIA SECESSION THROUGH REFERENDUM - Della Nurlaela (MIHI UMY, 2016)
Abstract This thesis discusses about the process and the reason behind referendum of Catalonia which demanding the independence and its secession from Spain. Since the day where Catalonia was still in the deep circle of history back to many years ago, Catalan people has been experienced many tensions that remains in their memories until now. The topic becomes more important because those historical aspect is one of the factors which triggering the willing of Catalonia to be independence and secede from Spain, especially in the era of Jendral Franco who ruled Spain which here will be elaborated more as one era where Catalan people got historical presures. The demands not only came from the government of Catalonia, but it also came from the majority of the people in Catalonia who are agreed to secede from Spain as an independence state. It is realized by the holding of a referendum which further evokes many contradictory arguments and rejections from several parties notably from the main government of Spain. Therefore, besides providing the whole story of Catalonia’s eagerness of secession, this thesis is also offers other views from Spain government which eventually leads to the raise of the protest from Catalan people toward the decision of Spain government and makes the dispute between Catalonia and Spain even more complicated. The desire of Catalan people who patiently waiting for a wise decision from Spain government to approve those desires bring the dispute comes up until now. Hence, the research question that limits the discussion for this topic questioning the reason behind the willing of Catalan people who asked for the secession and the running of Catalonia’s referendum. Then after several analyses, in the end this thesis gives a conclusion and the suggestion toward the problem of Catalonia’s secession.